The potential contribution of transition theory to the analysis of bioclusters and their role in the transition to a bioeconomy - Frans Hermans (Biofuels, Bioproducts and Biorefining, 2018)
Biocluster initiatives have become an important tool for governments to establish, promote, and strengthen economic collaboration, learning, innovation, and employment within particular regions. However, in addition to issues like competitiveness and employment, bioclusters operate with the additional goal of fostering the transition to a sustainable bioeconomy. The profound changes that are required for a successful shift from a fossil-based economy to a bioeconomy are called transitions and the relatively new scientific field of transition theory has emerged to study them. The aim of this paper is to show the contribution that transition theory can make to the study of bioclusters. In this paper I will review frameworks from the study of sustainability transitions (multi-level perspective and technical innovation systems) and frameworks from theories of evolutionary economic geography and cluster studies (regional and sectoral innovation systems). The review shows how the choice of a particular framework will shape the analysis of the biocluster through the particular focus and delineation associated with each framework. The review shows the advantages and disadvantages these frameworks have for incorporating the various issues related to the shift towards a bioeconomy that are currently neglected in the literature on bioclusters.
Keywords: 330; bioclusters; innovation; innovation systems; multi-level perspective (MLP); sustainability transitions